Debt to Equity Ratio, Fixed Asset Turnover and Profit Growth in Companies Listed on The BEI - Mursalini, Wahyu Indah; Sriyanti, Esi; Sari, Irma Permata (Journal of International Accounting, Taxation and Information Systems, 2024)
The aim of this research  is to investigate how the debt to equity ratio and fixed asset turnover impact the growth of profits. The focus of this research will be on analyzing the financial records of companies within the food and beverage industry that are traded on the Indonesia Stock Exchange from 2019 to 2022. A total of 48 companies will be included in the study. Purposive sampling was utilized to select 31 companies for the study. Quantitative data was employed for analysis. The findings indicate that the debt to equity ratio has a partial but significant impact on profit growth. This is evidenced by the research results that the t-count value> t table (-2.186> 1.987) and a significance value of 0.032 <0.05. Thus, H1 in this study is accepted. According to the test results, it was found that profit growth is not significantly impacted by fixed asset turnover. This is evidenced by the research results showing the t-count value <t-table (-0.742 <1.987) and a significance value of 0.460> 0.05. Thus, H2 is rejected in this research. The results of the study suggest that both the debt to equity ratio and fixed asset turnover do not collectively influence profit growth to a noticeable extent. The research findings clearly demonstrate a calculated f value <f table (2.402 <3.10) and a significance value of 0.097> 0.05. Thus, H3 in this study is rejected. The value of 0.053 or 5.3% demonstrates this, with the remaining 94.7% being affected by unexplored variables.